2004
DOI: 10.1213/01.ane.0000132543.65095.2c
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Among Portal Lactate, Intramucosal Sigmoid pH, and ΔCO2 (Paco2 − Regional Pco2) as Indices of Complications in Patients Undergoing Abdominal Aortic Aneurysm Surgery

Abstract: Our aim in this observational, prospective, noncontrolled study was to detect, in 29 patients who underwent abdominal aortic aneurysm (AAA) surgery, correlations between the incidence of postoperative organ failure and intraoperative changes in arterial and portal blood lactate; changes in intramucosal sigmoid pH (pHi); differences between sigmoid Pco(2) and arterial Pco(2) (DeltaCO(2)); and hemoglobin (Hb). Hb, arterial blood lactate concentrations, pHi, and DeltaCO(2) (air tonometry) were recorded at the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Björck et al 34 specified a sigmoid pHi of less than 7·1 as an early warning of ischaemic colitis after abdominal aortic surgery. A range of 6·86 to 7·30 has been reported in the literature 13,17 . Few reports, however, have noted cut-off points and accuracy for catheters placed within the colon.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Björck et al 34 specified a sigmoid pHi of less than 7·1 as an early warning of ischaemic colitis after abdominal aortic surgery. A range of 6·86 to 7·30 has been reported in the literature 13,17 . Few reports, however, have noted cut-off points and accuracy for catheters placed within the colon.…”
Section: Discussionmentioning
confidence: 94%
“…Bjork et al 34 reported a sensitivity and specificity of 100 per cent for predicting ischaemic colitis when a sigmoid pHi below 6·86 for longer than 4 h was registered. In addition, a sensitivity of 100 per cent, specificity of 92 per cent, positive predictive value of 80 per cent and negative predictive value of 92 per cent was found for predicting major complications when a sigmoid pHi below 7·1 was maintained for 2 h. Donati et al 13 found that a sigmoid pHi value of < 7·15 was a predictor of organ failure with a sensitivity of 92·3 per cent, a specificity of 68·8 per cent and positive and predictive values of 70·6 and 91·7 per cent, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…How therefore can, the elevated levels of gut luminal lactate be of clinical relevance? Lactate in the gut lumen is a marker of altered intestinal permeability [16], and in abdominal aortic surgery, elevated levels of lactate in the splanchnic circulation predict organ failure [13]. Our patients were chosen due to the known occurrence of altered permeability during CPB [1], and therefore we expected to detect increased levels of lactate in the gut lumen.…”
Section: Discussionmentioning
confidence: 99%
“…As tonometry has also been used for monitoring the colonic mucosa during aortic surgery [13] and during CPB [22], we also sought to compare that method with endoluminal microdialysis.…”
mentioning
confidence: 99%